Coronary CT Angiography vs Functional Stress Testing in Chest Pain Evaluation; A Meta-Analysis of Diagnostic Accuracy, Revascularization Rates, and Cost-Effectiveness - Mahmood, Abeeha; Faisal, Farhan; Alshamsi, Aisha Saleh; Farooq, Sana; Sajjad, Sonia; Khalid, Zonash; Malik, Moeed Akbar; Malik, Hafsa; Hamza, Asmaa; Wazir, Sumaira (Indus Journal of Bioscience Research, 2025)
Background: Chest pain is a common clinical feature and medical diagnostic dilemma in both emergency and outpatient care. There are two major non-invasive methods for the management of suspected CAD (coronary artery disease), coronary computed tomography angiography (CCTA), and functional stress testing (FST). With recent advancement in technologies CCTA has been identified as a good alternative for early triage but doubt still exits as to how this is superior in terms of diagnosis, as downstream therapeutic decisions as well as the monetary implications with former stress testing modalities. Objectives: This meta-analysis will provide comparison of CCTA and Functional stress testing with regard to (1) diagnostic accuracy for obstructive CAD, (2) rates of downstream revascularization and (3) overall cost-effectiveness in patients coming for evaluation of chest pain. Methodology: This study has been carried out, as systematic review and meta-analysis (in line with PRISMA guidelines). A total of 27 original studies published from 2007-2024 were included comprising randomized controlled trials and prospective cohort with direct comparisons of CCTA and FST. Searched databases were PubMed, Embase and Scopus. Estimates of sensitivity, specificity, and revascularization rates, and cost metrics were pooled using random effects model. Subgroup analyses were conducted, by risk stratification as well as clinical setting (acute stomach pain versus stable stomach pain). Results: CCTA showed greater pooled sensitivity (95.2%) and NPV (97.4%) than FST (sensitivity 79.1%, NPV 89.6%) for detection of obstructive CAD. The Revascularization rates were higher in CCTA group (14.6%) compared to FST group, (9.8%) inferring a direct route to invasive treatment over anatomically proven disease. Despite slight increase in cost of initial imaging, the CCTA was more cost-effective in terms of decreased downstream testing and shorter hospital stay as well as fewer non conclusive evaluations. Heterogeneity was low to moderate in all outcomes (I²> < 40%). Conclusion: CCTA is superior when it comes to diagnostic accuracy and it comes with higher corresponding rates of appropriate revascularization than functional stress testing. Although imaging costs may be more upfront, the net analysis of benefits vis-à- vis cost in the case of both emergency and outpatient chest pain analysis supports CCTA. The results also advocate a wider implementation of CCTA as a frontline diagnostic tool, including low-to-intermediate risk populations.